Persepsi Mahasiswa Terhadap Program Diet Plastik di DKI Jakarta Sebagai Upaya Penyelamatan Ekosistem Laut - Aulia'fi Jalatami; Tiara Putri; Ade Suryanda (ECOTAS, 2021)
The sea is considered a waste disposal place because of its large volume of water and the ability to dilute all kinds of foreign substances. The community has ignored marine pollution for many years and gradually causes pollution effects from waste disposal. More and more waste is being dumped into the sea and has a high concentration. If waste disposal into the sea is carried out sustainably, it is feared that it will cause global impacts from marine pollution. The purpose of this study was to determine student perceptions of the plastic diet program as an effort to save marine ecosystems. This study uses a qualitative descriptive method, with the distribution of questionnaires, with respondents being a student in DKI Jakarta. From the research results obtained from 31 samples, the perception of students studying in DKI Jakarta towards the plastic diet as an effort to save the marine ecosystem is very positive and supports the movement. This finding is evidenced by the student's knowledge of the importance of maintaining marine ecosystems, the dangers of plastic waste, and efforts to make the plastic diet program successful in DKI Jakarta.